Clinical Subgroups in Bilateral Meniere Disease - Frejo, Lidia; Soto-Varela, Andres; Santos-Perez, Sofía; Aran, Ismael; Batuecas-Caletrio, Angel; Perez-Guillen, Vanesa; Perez-Garrigues, Herminio; Fraile, Jesus; Martin-Sanz, Eduardo; Tapia, Maria C.; Trinidad, Gabriel; García-Arumi, Ana María; et al. (Frontiers in Neurology, 2016)
Meniere disease (MD) is a heterogeneous clinical condition characterized by sensorineural hearing loss, episodic vestibular symptoms and tinnitus associated with several comorbidities such as migraine or autoimmune disorders (AD). The frequency of bilateral involvement may range from 5-50% and it depends on the duration of the disease. We have performed a two-step cluster analysis in 398 patients with bilateral MD to identify the best predictors to define clinical subgroups with a potential different etiology to improve the phenotyping of bilateral MD and to develop new treatments. We have defined five clinical variants in bilateral MD. Group 1 is the most frequently found, includes 46% of patients, and is defined by metachronic hearing loss without migraine and without AD. Group 2 is found in 17% of patients, and it is defined by synchronic hearing loss without migraine or AD. Group 3, with 13% of patients, is characterized by familial MD, while group 4, that includes 12% of patients, is associated by the presence of migraine in all cases. Group 5 is found in 11% of patients and is defined by AD. This approach can be helpful in selecting patients for genetic and clinical research. However, further studies will be required to improve the phenotyping in these clinical variants for a better understanding of the diverse etiological factors contributing to bilateral MD.